Familial Hypercholesterolemia: Real-World Data of 1236 Patients Attending a Czech Lipid Clinic. A Retrospective Analysis of Experience in More than 50 years. Part II. Clinical Characteristics - Altschmiedova, Tereza; Todorovova, Veronika; Vrablik, Michal; Ceska, Richard (Frontiers in Genetics, 2022)
Introduction Patients with familial hypercholesterolemia (FH) are at increased risk of premature atherosclerotic cardiovascular disease (ASCVD). Aim of study To perform a retrospective analysis of data to assess the effects of individual lipoproteins and other risk factors (RFs) on the development of ASCVD and to compare these parameters in individuals with versus without ASCVD. Patients and methods Our study group included a total of 1236 patients with FH (395 men and 841 women with a mean age of 44.8 ± 16.7 years) attending a single lipid clinic. The diagnosis of FH was established using the Dutch Lipid Clinic Network Criteria (DLCNC). Among the 1236 FH patients, 1008 of them [854 suspected with LDL receptor-mediated FH and 154 with familial defective apolipoprotein B-100 (FDB)] were genetically analysed. Their RFs were assessed based on the patients’ clinical characteristics. Results While patients with ASCVD had higher baseline LDL-C, TC, TG and Lp(a) compared with patients without this diagnosis, this ratio was just the opposite by the follow-up. The highest statistically significant differences were seen in the baseline levels of Lp(a) and, quite surprisingly, TG. Except for Lp(a), the levels of all lipid parameters declined significantly over time. While the incidence of diabetes and arterial hypertension was not higher in our group compared with the general population, these patients were at a more significant risk of ASCVD. Conclusion Familial hypercholesterolemia is a major RF for the development of ASCVD. While our analysis confirmed the important role of LDL-C, it also corroborated a strong correlation between ASCVD and other lipid parameters, and Lp(a) and TG in particular. Familial hypercholesterolemia is not the only RF and, to reduce cardiovascular risk of their patients, physicians have to search for other potential RFs. Patients diagnosed to have FH benefit from attending a specialized lipid clinic per se.